1997
DOI: 10.1200/jco.1997.15.1.297
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-gemcitabine combination in advanced non-small-cell lung cancer: a phase II study.

Abstract: The combination of gemcitabine and cisplatin induced a high response rate in both stage IIIB and IV NSCLC, with modest side effects. The regimen deserves further careful evaluation in a phase III prospective randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
114
1
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(121 citation statements)
references
References 12 publications
5
114
1
1
Order By: Relevance
“…Alternative schedules have been described for a variety of tumours. Some investigators have given cisplatin on days 2 or 15 of a 28 day cycle (Abratt et al, 1997;Crino et al, 1997), or split the cisplatin dose for days 1, 8 and 15 (Shepherd et al, 1997(Shepherd et al, , 2000. Others have shortened the cycle to 21 days, administering cisplatin on day 1 (Rosell et al, 1998) or days 1 and 8 (Nagourney et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Alternative schedules have been described for a variety of tumours. Some investigators have given cisplatin on days 2 or 15 of a 28 day cycle (Abratt et al, 1997;Crino et al, 1997), or split the cisplatin dose for days 1, 8 and 15 (Shepherd et al, 1997(Shepherd et al, , 2000. Others have shortened the cycle to 21 days, administering cisplatin on day 1 (Rosell et al, 1998) or days 1 and 8 (Nagourney et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…10 -12 When combined with cisplatin and/or paclitaxel or vinorelbine, gemcitabine therapy shows an objective response rates in 28 -54% and the median survival durations ranged from 38 to 61.5 weeks. [13][14][15][16][17][18] However, the treatment of advanced lung cancer still remains a challenge to medical oncologists.…”
Section: Abstract: Apoptosis; Vesicular Stomatitis Virus; Gemcitabinmentioning
confidence: 99%
“…10 -12 When combined with cisplatin and/or paclitaxel or vinorelbine, gemcitabine therapy shows an objective response rates in 28 -54% and the median survival durations ranged from 38 to 61.5 weeks. [13][14][15][16][17][18] However, the treatment of advanced lung cancer still remains a challenge to medical oncologists.Because of differences in mechanisms of action and toxicity profiles, the combination of the above 2 agents may have clinical potential. The present study was designed to determine whether gemcitabine potentiates the antitumor activity of VSV in vitro using both A549 (human lung adenocarcinoma) and LLC (murine Lewis lung carcinoma) cell lines and in vivo using A549 lung cancer xenografts and the murine syngeneic Lewis lung cancer, and if so, to examine the possible mechanism in the phenomenon, as well as to provide some potential implications for the treatment of human lung cancer.…”
mentioning
confidence: 99%
“…In phase II studies, 26 -54% stage IIIB/IV NSCLC patients responded to GC treatment. Good median and 1-year survival have been consistently observed (Abratt et al, 1997;Crino et al, 1997;Einhorn, 1997;Shepherd et al, 1997). Three randomized phase III studies demonstrated the superiority of GC over other chemotherapy regimens (Cardenal et al, 1999;Crino et al, 1999;Sandler et al, 2000).…”
mentioning
confidence: 98%